2022
DOI: 10.1111/ans.17722
|View full text |Cite
|
Sign up to set email alerts
|

Use of telemedicine consultations in head and neck cancer: patient perceptions, acceptability and accessibility

Abstract: Backgrounds: Telemedicine has been effective in the management of various medical conditions, however, there is limited knowledge of its use in head and neck oncosurveillance. This is of importance currently while trying to mitigate the risk of transmission during the COVID-19 pandemic. This study aims to evaluate acceptability, satisfaction and perceptions of telemedicine technology among outpatients for head and neck oncologic surveillance. Methods: A cross-sectional study was conducted for head and neck sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Whilst it could be postulated that elective, low acuity Oral and Maxillofacial Surgery settings are adaptable to the Telemedicine setting, for the urgent patient, face-to-face appointments are important due to the sensitive nature of information to be delivered, especially in the initial appointment setting. Dhillon et al [6 ▪▪ ] noted in their cross-sectional study that 65% of Head and Neck cancer patients surveyed identified the lack of physical examination as an issue. Although several studies have shown high levels of satisfaction with Telehealth consults, there is limited evidence in relation to the factors affecting patient outcomes, for example, length of stay, complication rate or morbidity and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it could be postulated that elective, low acuity Oral and Maxillofacial Surgery settings are adaptable to the Telemedicine setting, for the urgent patient, face-to-face appointments are important due to the sensitive nature of information to be delivered, especially in the initial appointment setting. Dhillon et al [6 ▪▪ ] noted in their cross-sectional study that 65% of Head and Neck cancer patients surveyed identified the lack of physical examination as an issue. Although several studies have shown high levels of satisfaction with Telehealth consults, there is limited evidence in relation to the factors affecting patient outcomes, for example, length of stay, complication rate or morbidity and mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to explore our patients' positions on telemedicine (if all technical barriers such as computers and sufficient internet connection had been addressed). Following the COVID-19 pandemic, telemedicine has gained more interest, and studies from the United States, Australia, and the Netherlands have also proven that HNC patients are positive towards telemedicine as a part of the outpatient monitoring, but the lack of physical evaluation remains a limitation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This shift enables patients to conveniently discuss their concerns, receive updates, and obtain medical advice from the comfort of their homes. 75 Furthermore, the incorporation of highdefinition video technology has enabled meticulous visual examinations, affording healthcare providers the ability to assess surgical sites and monitor postoperative healing remotely. This technological innovation has yielded enhancements in diagnostic precision and contributed to a reduction in the requirement for physical examinations, as evidenced in a study that compared video-based free flap assessment following head and neck free tissue transfer to in-person evaluations.…”
Section: Personalized Treatment and Follow-up Advances In Head And Ne...mentioning
confidence: 99%
“…Telemedicine platforms have empowered healthcare providers to conduct virtual consultations, thereby diminishing the necessity for in‐person visits. This shift enables patients to conveniently discuss their concerns, receive updates, and obtain medical advice from the comfort of their homes 75 . Furthermore, the incorporation of high‐definition video technology has enabled meticulous visual examinations, affording healthcare providers the ability to assess surgical sites and monitor postoperative healing remotely.…”
Section: Forging a Path To Enhanced Communication And Patient Care In...mentioning
confidence: 99%